A ratiometric electrochemical biosensor for ultrasensitive and highly selective detection of the K-ras gene via exonuclease III-assisted target recycling and rolling circle amplification strategies. Issue 32 (29th July 2019) - Xiao, Qi; Feng, Jinrong; Li, Jiawen; Liu, Yi; Wang, Dan; Huang, Shan
Abstract : A ratiometric electrochemical biosensor for ultrasensitive and highly selective detection of the K-ras gene via Exo III-assisted target recycling and RCA strategies. Abstract : An effective ratiometric electrochemical biosensing platform was developed for ultrasensitive and highly specific detection of the K-rat sarcoma (K-ras) gene via exonuclease III (Exo III)-assisted target recycling and rolling circle amplification (RCA) strategies. The ferrocene-modified hairpin capture probe (Fc-HP-SH) labeled with ferrocene (Fc) at the 3′ terminus and a thiol group at the 5′ terminus and a padlock probe were chosen to fabricate the ratiometric electrochemical biosensor. Fc-HP-SH self-assembled on the surface of a gold electrode through the Au–S bond, and 6-mercaptohexanol was added to block the unspecific adsorption sites on the gold electrode surface. In the presence of the target K-ras gene and Exo III, the K-ras gene specifically hybridized with the specific 3′ terminal sequences of Fc-HP-SH to open the hairpin structure. Meanwhile, Exo III cleaved the DNA duplex to release the target K-ras gene for the target recycling process. The residual single-stranded oligomers were elongated during the RCA process, and hemin specifically bound with these long oligonucleotides to form a stable G-quadruplex/hemin complex. Consequently, the variations of the differential pulse voltammetry (DPV) peak currents of Fc ( I Fc ) and the G-quadruplex/hemin complex ( I G-quadruplex/hemin ) resulted in an obvious increase of the ratio of DPV peak currents I G-quadruplex/hemin / I Fc . Under optimum experimental conditions, the dynamic response range was in the range of 0.5 fM to 10 pM with a detection limit of 0.28 fM (S/N = 3). This method highly recognized the target K-ras gen and its mutants, and such method was successfully applied in human serum samples. The proposed method possesses potential applications in monitoring of serious diseases and clinical molecular diagnosis.